Prestressed concrete safety precautions in post-tensioning. (Thomas Telford, 1989)
Post-tensioning and grouting operations can be dangerous if the required care is not taken in planning, in site preparations and in execution. This guide to good practice highlights safety measures which are particularly applicable to pre-stressed concrete, dealing with precautions necessary for post-tensioning and grouting operations on site.
Keywords: Post-tensioned prestressed concrete.; elektronické knihy; electronic books